From Kant to Lévi-Strauss : the background to contemporary critical theory - Simmons, Jon (Edinburgh University Press, 2002)
Aimed at students without philosophical training and who study literary, cultural, social or political theorists engaging with this European intellectual tradition, this textbook is an accessible guide to key figures in "The Tradition of Critique"--Critical post-Enlightenment European thinking